Activation of paramyxovirus membrane fusion and virus entry - Jardetzky, Theodore S; Lamb, Robert A (Current opinion in virology, 2014)
•Most paramyxoviruses require attachment and fusion (F) proteins for cell entry.•Competing ‘clamp’ and ‘provocateur’ models have been proposed as entry mechanisms.•Attachment proteins contain receptor-binding (RBD) and stalk domains that activate F.•Attachment protein RBD and stalk domains interact, potentially regulating F activation.•Headless stalk constructs, lacking RBDs, constitutively activate F mediated fusion.•Accumulating data favor a general ‘provocateur’ model for F protein activation. The paramyxoviruses represent a diverse virus family responsible for a wide range of human and animal diseases. In contrast to other viruses, such as HIV and influenza virus, which use a single glycoprotein to mediate host receptor binding and virus entry, the paramyxoviruses require two distinct proteins. One of these is an attachment glycoprotein that binds receptor, while the second is a fusion glycoprotein, which undergoes conformational changes that drive virus-cell membrane fusion and virus entry. The details of how receptor binding by one protein activates the second to undergo conformational changes have been poorly understood until recently. Over the past couple of years, structural and functional data have accumulated on representative members of this family, including parainfluenza virus 5, Newcastle disease virus, measles virus, Nipah virus and others, which suggest a mechanistic convergence of activation models. Here we review the data indicating that paramyxovirus attachment glycoproteins shield activating residues within their N-terminal stalk domains, which are then exposed upon receptor binding, leading to the activation of the fusion protein by a ‘provocateur’ mechanism.